Approaches to surface engineering of extracellular vesicles - Richter, Maximilian; Vader, Pieter; Fuhrmann, Gregor (Advanced Drug Delivery Reviews, 2021)
Extracellular vesicles (EVs) are cell-derived nanoparticles that are important mediators in intercellular communication. This function makes them auspicious candidates for therapeutic and drug-delivery applications. Among EVs, mammalian cell derived EVs and outer membrane vesicles (OMVs) produced by gram-negative bacteria are the most investigated candidates for pharmaceutical applications. To further optimize their performance and to utilize their natural abilities, researchers have strived to equip EVs with new moieties on their surface while preserving the integrity of the vesicles. The aim of this review is to give a comprehensive overview of techniques that can be used to introduce these moieties to the vesicle surface. Approaches can be classified in regards to whether they take place before or after the isolation of EVs. The producing cells can be subjected to genetic manipulation or metabolic engineering to produce surface modified vesicles or EVs are engineered after their isolation by physical or chemical means. Here, the advantages and disadvantages of these processes and their applicability for the development of EVs as therapeutic agents are discussed.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Drug delivery; Exosomes; Extracellular vesicles; Fluorescent labeling; Outer membrane vesicles; Surface functionalization; Targeting